Leisure Boredom dan Kecenderungan Kecanduan Media Sosial Tik Tok pada Gen Z - Sofi Pappa; Herlan Pratikto; Akta Ririn Aristawati (Universitas Muhammadiyah Purwokerto, 2024)
This study aims to analyze the relationship between leisure boredom and the tendency of social media addiction to TikTok among Generation Z. This research employs a quantitative approach using a correlational method. The sampling technique used is purposive sampling, with a total of 120 participants from Generation Z. Measurements were conducted using the TikTok social media addiction scale and the leisure boredom scale. The data analysis results using Product Moment correlation indicate a significant and strong relationship between leisure boredom and the tendency for TikTok social media addiction among Generation Z. These findings suggest that the higher the level of leisure boredom, the greater the tendency for individuals to develop social media addiction to TikTok. Based on these findings, it is recommended that Generation Z engage in more diverse and meaningful activities during their leisure time to reduce the risk of social media addiction. Additionally, parents, educators, and relevant stakeholders should provide education on time management and healthy social media usage. Future research can explore other contributing factors to social media addiction, such as self-regulation and social support, to gain a more comprehensive understanding of the issue.